Volterra-series-based nonlinear system modeling and its engineering applications: A state-of-the-art review. (15th March 2017) - Cheng, C.M.; Peng, Z.K.; Zhang, W.M.; Meng, G.
Abstract: Nonlinear problems have drawn great interest and extensive attention from engineers, physicists and mathematicians and many other scientists because most real systems are inherently nonlinear in nature. To model and analyze nonlinear systems, many mathematical theories and methods have been developed, including Volterra series. In this paper, the basic definition of the Volterra series is recapitulated, together with some frequency domain concepts which are derived from the Volterra series, including the general frequency response function (GFRF), the nonlinear output frequency response function (NOFRF), output frequency response function (OFRF) and associated frequency response function (AFRF). The relationship between the Volterra series and other nonlinear system models and nonlinear problem solving methods are discussed, including the Taylor series, Wiener series, NARMAX model, Hammerstein model, Wiener model, Wiener-Hammerstein model, harmonic balance method, perturbation method and Adomian decomposition. The challenging problems and their state of arts in the series convergence study and the kernel identification study are comprehensively introduced. In addition, a detailed review is then given on the applications of Volterra series in mechanical engineering, aeroelasticity problem, control engineering, electronic and electrical engineering. Highlights: The basic definition of Volterra series is introduced. Some frequency domain concepts derived from the Volterra series are given. The relationship between the series and other models and methods are discussed. The convergence and kernel identification study are comprehensively introduced. A detailed review is given on the applications of Volterra series in engineering.